2022
DOI: 10.1097/tp.0000000000004047
|View full text |Cite
|
Sign up to set email alerts
|

Clamping of the Aortic Arch Vessels During Normothermic Regional Perfusion After Circulatory Death Prevents the Return of Brain Activity in a Porcine Model

Abstract: Background. The cerebral effect of clamping following normothermic regional perfusion (NRP) in donation after circulatory death (DCD) remains unknown. We investigated the effect of cerebral reperfusion during NRP and the preventive effect of clamping on brain function in a porcine model. Methods. In 16 pigs, intracranial physiological parameters were recorded, including pressure, cerebral blood perfusion (CBF), temperature, and oxygen. Additionally, electroencephalography (EEG) and somatosensory evoked poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…5 We confirmed restoration of brain activity in a study of cerebral perfusion and activity following DCD and NRP in the animals from the present study. 7 We found that cerebral reperfusion restored some kind of cerebral activity in all animals in the nonclamp group. Ethics mandate to uphold the permanence of death by AAV clamping when performing TA-NRP‚ and we have now shown no negative cardiac or inflammatory effects of AAV clamping during NRP.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…5 We confirmed restoration of brain activity in a study of cerebral perfusion and activity following DCD and NRP in the animals from the present study. 7 We found that cerebral reperfusion restored some kind of cerebral activity in all animals in the nonclamp group. Ethics mandate to uphold the permanence of death by AAV clamping when performing TA-NRP‚ and we have now shown no negative cardiac or inflammatory effects of AAV clamping during NRP.…”
Section: Discussionmentioning
confidence: 62%
“…Controversially, reperfusion of the brain has shown to restore some brain activity in pigs. 7 Following this finding, we have demonstrated that clamping of the aortic arch vessels (AAVs) sufficiently prevents restoration of cerebral blood flow and electrical activity. 7 However, little is known about the hemodynamic and inflammatory effects following clamping of the AAV in relation to DCD donation.…”
Section: Introductionmentioning
confidence: 91%
“…In the current issue, Dalsgaard et al 9 demonstrate that clamping of aortic arch vessels in a pig model of NRP is sufficient to prevent resumption of cortical blood flow, cortical electrical activity, and brain stem function during NRP. The authors prospectively randomized 16 female pigs to clamping of aortic arch vessels versus sham surgery during NRP.…”
mentioning
confidence: 88%
“…These techniques have been extensively discussed by a number of expert groups in the UK, Canada, and other countries [ 63 ]. After confirmation of death in DCD and before starting normothermic regional perfusion (NRP), it is considered appropriate to perform surgery to ligate or divide the aortic arch vessels for cases with thoracic NRP or to occlude the descending aorta for abdominal NRP [ 65 ]. Opening the vessels of the supra-aortic arch to the atmosphere ensures that there is no reperfusion to the brain.…”
Section: Regional Normothermic Perfusionmentioning
confidence: 99%